Influence of acid-sensing ion channel blocker on behavioral responses in a zebrafish model of acute visceral pain (2022)
Acid-sensing ion channels (ASICs) play significant roles in numerous neurological and pathological conditions, including pain. Although acid-induced nociception has been characterized previously in zebrafish, the contri- bution of ASICs in modulating pain-like behaviors is still unknown. Here, we investigated the role of amiloride, a nonselective ASICs blocker, in the negative modulation of specific behavioral responses in a zebrafish-based model of acute visceral pain. We verified that intraperitoneal injection (i.p.) of 0.25, 0.5, 1.0, and 2.0 mg/mL amiloride alone or vehicle did not change zebrafish behavior compared to saline-treated fish. Administration of 2.5% acetic acid (i.p.) elicited writhing-like response evidenced by the abnormal body curvature and impaired locomotion and motor activity. Attenuation of acetic acid-induced pain was verified at lower amiloride doses (0.25 and 0.5 mg/mL) whereas 1.0 and 2.0 mg/mL abolished pain-like responses. The protective effect of the highest amiloride dose tested was evident in preventing writhing-like responses and impaired locomotion and vertical activity. Collectively, amiloride antagonized abdominal writhing-like phenotype and aberrant behaviors, supporting the involvement of ASICs in a zebrafish-based model of acute visceral pain